Mental Health Challenges and Their Association With Financial Priority and Nutrition Among University Students in Bangladesh: A Cross‐Sectional Study - Marjia Sultana; Towhid Hasan; Nishat Subah Tithi; Nibadita Majumder; Md. Mahmudul Hasan Shohag (Health Science Reports, 2026)
ABSTRACT Background and Aims University students represent a dynamic and diverse population, navigating a critical period of personal growth, academic challenges, and engaging with a wide variety of new people. However, they often face significant mental health challenges, including anxiety, depressive, and insomnia symptoms, which are exacerbated by academic pressures, financial stress, and poor dietary habits. Hence, this research sought to examine the prevalence of mental health issues among university students in Bangladesh and explore potential links between these issues and financial prioritization and nutrition. Methods This cross‐sectional survey was carried out among 450 students attending Noakhali Science and Technology University (NSTU), Bangladesh using a structured questionnaire. Anxiety, depressive, and insomnia symptoms were assessed using the Generalized Anxiety Disorder‐7 (GAD‐7), Patient Health Questionnaire‐9 (PHQ‐9), and Athens Insomnia Scale‐8 (AIS‐8), respectively. Nutritional behavior was assessed using the Health Promoting Lifestyle Profile‐II (HPLP‐II) nutrition subscale, and financial priority was evaluated using a culturally adapted version of the Castellanos and Holcomb financial prioritization instrument. Multivariable linear regression was used to examine the associations between financial priority and mental health outcomes, whereas multivariable logistic regression was used to assess the associations between nutrition and mental health outcomes. Results The prevalence of anxiety, depressive, and insomnia symptoms was 78.9%, 90.4%, and 63.6%, respectively, Anxiety, depressive, and insomnia symptoms were significantly interconnected, with positive associations between anxiety and depressive symptoms (β = 0.154, p < 0.001), anxiety and insomnia symptoms (β = 0.183, p < 0.001), and depressive and insomnia symptoms (β = 0.192, p < 0.001). Most students prioritized spending on food (84.4%) and clothing (71.3%). In multivariable linear regression analyses, prioritizing food was associated with lower anxiety ( b = −2.153, p < 0.001), depressive ( b = −1.743, p = 0.018), and insomnia ( b = −3.519, p < 0.001) symptom scores. Conversely, prioritizing smoking was associated with increased mental health issues ( p < 0.001). In multivariable logistic regression analyses, good nutrition was associated with reduced odds of anxiety (adjusted odds ratio [AOR]: 0.501, p = 0.012) and depressive (AOR: 0.425, p = 0.025) symptoms, but higher odds of insomnia symptoms (AOR: 2.03, p = 0.002). Conclusions These findings highlight the intricate relationships between financial priorities, nutrition, and psychological well‐being among Bangladeshi university students, emphasizing the need for importance of developing targeted interventions and support systems.